Facies architecture of asymmetrical branching distributary channels: Cretaceous Ferron Sandstone, Utah, USA. Issue 5 (21st March 2014) - Li, Yangyang; Bhattacharya, Janok; Mountney, Nigel
Abstract Distributary channel systems are an important component of deltaic systems, but details of their branching pattern, stream‐order, internal variability and relation with adjacent levée, bay and bayhead delta are rather poorly documented in ancient examples. Photomosaic and measured sections collected along a gooseneck‐shaped canyon in southern Utah allow direct mapping of the branching pattern of an ancient distributary system. The main channel belt is ca 250 m wide and narrows to ca 200 m downstream of the branching point. A subordinate channel belt, ca 80 m wide, branches off of the main channel, forming a distinctly asymmetrical branching pattern. Water discharge in the main channel is estimated to be 85 to 170 m3 sec−1. Comparison with palaeodischarge estimates of trunk rivers mapped in previous studies suggests that the branching documented in this study probably is a fourth‐order split. The distributary channels are characterized by a U‐shaped geometry filled with medium‐grained, cross‐bedded sandstone, and are dominated by lateral accretion, suggesting limited lateral migration and moderate sinuosity. Tidally influenced facies and limited trace fossils indicate direct marine influence. The distributary channels erode into adjacent levée and underlying heterolithic bay‐fill deposits, and the marine influence suggests that they were deposited on a lower delta plain, rather than on a non‐marine floodplain. The subordinate channel fed a bayhead delta, suggesting that it was formed by a partial avulsion, rather than bifurcation around a mouth bar, as is more characteristic of terminal distributary channels. Channel‐floor drapes, bar‐accretion drapes and abandoned channel fills within the sandstone channel belts represent the most important heterogeneity from the perspective of reservoir characterization.